Something To Hide : Inspector Lynley # 21 - George, Elizabeth, 1949- ([New York] : Viking, 2022)
"Detective Sergeant Barbara Havers and Detective Inspector Thomas Lynley are back in the next Lynley novel from #1 New York Times bestselling author Elizabeth George. When a police detective is taken off life support after falling into a coma, only an autopsy reveals the murderous act that precipitated her death. She'd been working on a special task force within North London's Nigerian community, and Acting Detective Superintendent Thomas Lynley is assigned to the case, which has far-reaching cultural associations that have nothing to do with life as he knows it. In his pursuit of a killer determined to remain hidden, he's assisted by Detective Sergeants Barbara Havers and Winston Nkata. They must sort through the lies and the secret lives of people whose superficial cooperation masks the damage they do to one another"--.
Keywords: Mystery fiction